Penerapan Rekaman Kaset sebagai Media Alternatif untuk Meningkatkan Hasil Belajar pada Materi Kimia Lingkungan dengan Pokok Bahasan Pencemaran Lingkungan Kelas XI SMA N. 14 Padang - Jumriana Rahayu; Eliyarti Eliyarti (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
Abstract The teaching and learning process will be more effective and efficient if supported by the right media. Research has been conducted to see the learning outcomes of students in class XI of SMA 14 by using cassette recording media as an alternative learning media in environmental chemistry material with the subject matter of the subject of environmental pollution. This research is a classroom action research (CAR) which is carried out in class XI students. Data collection techniques used are observation, tests and documentation. The data analysis technique is in the form of qualitative data and quantitative data. The results of data analysis show that classical completeness in the first cycle is 70%. While classical completeness in cycle II is 95%. This means that student learning outcomes from cycle I to cycle II increased by 25%. Based on the results of these studies it can be concluded that the application of cassette recordings as an alternative media can improve student learning outcomes in environmental chemistry subject matter of environmental pollution in Padang 14 High School. Keywords: Teaching Media, Cassette Records, Children's Learning Habits and Learning Outcomes and Environmental Pollution.